2015
DOI: 10.1210/jc.2015-2123
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Profile Through Life in Women With Polycystic Ovary Syndrome: A Nordic Multicenter Collaboration Study

Abstract: Context: Women with polycystic ovary syndrome (PCOS) have increased androgen secretion throughout fertile life; however, the data on the effect of menopause on hyperandrogenemia in these women are scarce. Nevertheless, large comprehensive comparative studies on age-related androgen levels in women with PCOS are lacking. Objective:The objective of the study was to investigate the effect of age on serum androgen levels in women with PCOS and to determine cutoff values for androgens and SHBG associated with a PCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
51
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 42 publications
8
51
2
3
Order By: Relevance
“…Finally, assuming that the AMH cutpoints for PCOS are similar in women with and without type 1 diabetes, perhaps women with type 1 diabetes less commonly have PCOS than women without diabetes. Since ovarian hormones decline with age among women with PCOS (36), these differences are less marked between women with and without diabetes at older ages.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, assuming that the AMH cutpoints for PCOS are similar in women with and without type 1 diabetes, perhaps women with type 1 diabetes less commonly have PCOS than women without diabetes. Since ovarian hormones decline with age among women with PCOS (36), these differences are less marked between women with and without diabetes at older ages.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced insulin resistance in obesity was reflected in the decrease in the SHBG levels particularly in the obese PCOS subjects resulting in an increased FAI. There is little data on the role ADTG in PCOS and androgen metabolism, however this study showing the increased ADTG: DHEAS ratio in obese PCOS using state of the art measurement free from assay interference addresses the discrepancy noted in one study that it was not correlated with PCOS [8, 18], and with another suggesting that ADTG levels are increased [13]. …”
Section: Discussionmentioning
confidence: 74%
“…It has been shown that conversion of DHEAS to ADTG occurs mainly through hepatic 5α-reductase activity, and to a lesser extent peripheral 5α-reductase activity [911]. It is reported that hepatic 5α-reductase activity is increased in insulin resistant states [18] and it can be seen from the results that the obese PCOS patients were significantly more insulin resistant than the non-obese PCOS patients and the normal controls (the HOMA-IR did not differ between the non-obese PCOS and normal subjects) suggesting that the increased insulin resistance in obesity may be driving the hepatic 5α-reductase activity converting DHEAS to ADTG. The enhanced insulin resistance in obesity was reflected in the decrease in the SHBG levels particularly in the obese PCOS subjects resulting in an increased FAI.…”
Section: Discussionmentioning
confidence: 99%
“…According to research, these parameter elevations are commonly utilised as hyperandrogenaemia biomarkers in PCOS (Pinola et al, 2015). This suggests that PCOS is regarded as a disorder caused by increased androgen biosynthesis, usage or metabolism as reiterated by Azziz et al (2006).…”
Section: Discussionmentioning
confidence: 99%